Evaluación económica para el uso y comercialización de los excedentes de gas natural en la región piura. - Rodríguez Rodríguez, Heidy Rosa (2012)
This research work was carried out a descriptive study of the economic feasibility of the surplus of natural gas in the north, in order to obtain preliminary studies for the use and marketing of oil. In conducting the economic evaluation were considered two alternative projects, to analyze these alternatives we got the information from the reports of daily production in 2011 from wells located in the San Pedro district of Talara Lobitos, belonging to the oil company Savia, Blowout and located in the Talara Alto district, belonging to the oil company Petrobras, so also do an analysis of a project involving parameters such as production costs, administrative costs, transportation, etc. By reducing the burning of natural gas surplus, it would minimize CO2 emissions therefore also reduces the volume of greenhouse gases causing climate change and would help preserve the environment.